Research recast(ed): S2E10 - Consumer behavior, black toilet paper, and the concept of weirdness with Dr. Claire Deng - Miskiman, Megan; Schabert, Reinette; Deng, Qian (My University, 2023)
In today’s episode, assistant professor of marketing here at MacEwan University - Dr. Claire Deng - discusses her research in consumer behaviour, the concept of weirdness, and the importance of market research.
Keywords: consumer behaviour; market research